Republic of Poland : Financial Sector Assessment Program-Technical Note-Stress Testing and Systemic Risk Analysis. (IMF Staff Country Reports; Country Report, 2019)
This Technical Note on Stress Testing and Systemic Risk Analysis for the Republic of Poland discusses that Poland's financial system is dominated by the banking sector, with significant state participation and foreign ownership. The banking system shows resiliency to adverse shocks in the aggregate, however, some other systemically important institutions (OSIIs) show weakness. While the adverse retail event had a limited impact, the wholesale event affected some large banks in the system. Interbank analyses showed that any destabilization to affiliating banks could cause severe distress to the affiliated cooperative banks. This finding strengthens the reasons for the authorities to address identified weaknesses in the affiliating banks. Moreover, banks large holdings of sovereign bonds and the substantial presence of state-controlled banks cause a significant sovereign-bank nexus in Poland. In order to avoid incentives for banks to hold sovereign debt, the Financial Sector Assessment Program team recommends that the Financial Institution Asset Tax is redesigned on grounds of both financial stability and efficiency.